Regulasi Perbankan Syariah: Studi Komparatif Antara Malaysia Dan Indonesia - M. Shabri Abd. Majid (Media Syari'ah, 2017)
Regulation plays a pivotal role in the development and sustainability of the Islamic banks w o r l d w i d e a s i t lays do wn the foundation on which the mechanics of the I slamic banking industr y. This study attempts to comparatively evaluate the regulations of Islamic banking in Malaysia and its neighbouring country, Indonesia. The study also assesses the extent to which the differences in regulations have contributed to the emergence and development of Islamic banks in the countries. The study found that the Islamic banking legal frameworks have significantly and positively affected the development of Islamic banking industry. The Islamic banking industry in Malaysia has developed more rapidly as compared the Islamic banks in Indonesia. This is due partly to the more comprehensives of the Islamic banking regulations enacted in Malaysia compared to Indonesia. This implies that to develop and ensure the sustainability of the Islamic banking industry more rapidly in Indonesia, the government has to enact the sound Islamic banking-related regulations.